Overselling democracy–claiming legitimacy? The link between democratic pretention, notions of democracy and citizens' evaluations of regimes' democraticness - Brunkert, Lennart J. (Frontiers in Political Science, 2022)
Many non-democratic countries anchor the word “democracy” in their national constitutions and everyday rhetoric, while ignoring the conceptual roots of democracy and its scholarly-defined procedural standards. This article argues that governments intentionally “oversell” democracy to their people, in order to exploit the legitimizing effect that the word embodies. This can, however, only succeed if the receiving side is susceptible to such claims to legitimacy. Accordingly, this study investigates how effective “overselling” attempts are in light of individuals' liberal vs. illiberal notions of democracy. Building on congruence theory, it juxtaposes the, at times blatant, “overselling” with individual-level notions of democracy and, thus, investigates whether governments' attempts to claim democratic-procedural legitimacy are contingent on citizens' understanding of the concept. Using multilevel moderation analyses, it shows that illiberal, authoritarian notions of democracy can convert “overselling” into positive evaluations of a regime, whereas prevailing liberal notions unmask “overselling” governments and create additional criticality. The conclusion argues that notions of democracy function as a filter, which matches true and false demand and supply of democracy. The findings help to understand why and how democratization movements can unfold and why some citizens see their country as democratic even though it is not.